The Safety Education (Pendidikan Keselamatan) di Sekolah Menengah Atas - Sari, Kristiana Wulan; Widowati, Evi (Jurusan Ilmu Kesehatan Masyarakat, Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang, Indonesia, 2020)
Road traffic injury is the leading cause of death among children aged 15-19 years old who are included in the education group level of Senior High School. The purpose of this research is to determine the overview of the application of safety education in Senior High School. This type of research is descriptive qualitative with 15 research subjects determined by purposive sampling technique. The research instrument uses interview guides, observation sheets, and document study sheets. The results obtained by an appropriate assessment indicator on the main factors of learning amounted to 69.24%, an appropriate assessment indicator on human factors is 59%, and an appropriate assessment indicator on facilities and infrastructure factors is 92%. Appropriate assessment indicators, with the largest percentage were found in the Instructional Materials and Infrastructures Sport component by 100%. Assessment indicators that are not appropriate, with the largest percentage was found in the Student component by 38.9%. While the assessment indicators are not available, the largest percentage is in the curriculum component by 40%. The implementation of safety education in Senior High School 3 Pati is still lacking.